Novel Mutation in the PKHD1 Gene Diagnosed Prenatally in a Fetus with Autosomal Recessive Polycystic Kidney Disease - Pankaj Thakur; Paul Speer; Aleksandar Rajkovic (Case Reports in Genetics)
We report a 29-year-old gravida 2, para 0100, who presented at 19 weeks and 4 days of gestation for ultrasound to assess fetal anatomy. Routine midtrimester fetal anatomy ultrasound revealed enlarged, hyperechoic fetal kidneys and normal amniotic fluid index. Follow-up ultrasound at 23 weeks and 5 days revealed persistently enlarged, hyperechoic fetal kidneys. Progressive oligohydramnios was not evident until 29 weeks of gestation, with anhydramnios noted by 35 weeks of gestation. Amniocentesis was performed for karyotype and to search for mutations in the PKHD1 for the presumptive diagnosis of autosomal recessive polycystic kidney disease (ARPKD). In our patient, a maternally inherited, previously reported pathogenic missense mutation in the PKHD1 gene, c.10444C>T, was identified. A second, previously unreported de novo mutation, c.5909-2delA, was also identified. This mutation affects the canonical splice site and is most likely pathogenic. Our case highlights PKHD1 allelic heterogeneity and the importance of genetic testing in the prenatal setting where many other genetic etiologies can phenocopy ARPKD.